Direct Synthesis of N-Protected Serine- and Threonine-Derived Weinreb Amides via Diboronic Acid Anhydride-Catalyzed Dehydrative Amidation: Application to the Concise Synthesis of Garner’s Aldehyde - Shimada, Naoyuki; Ohse, Naoki; Takahashi, Naoya; Urata, Sari; Koshizuka, Masayoshi; Makino, Kazuishi (Synlett, 2021)
An efficient method for the direct synthesis of Weinreb amides derived from serine and threonine derivatives via diboronic acid anhydride-catalyzed hydroxy-directed amidation is described. This is the first successful example of the synthesis of serine- or threonine-derived Weinreb amides using catalytic dehydrative amidations. The methodology could be applied to the concise synthesis of Garner’s aldehyde.
Keywords: dehydrative amidation; Weinreb amide; Garner’s aldehyde; organoboron catalysis; diboronic acid anhydride; hydroxy-directed reaction